AKOMODASI NILAI-NILAI KONSERVASI DALAM PENYELESAIAN PERKARA PIDANA (STUDI KASUS DI MASYARAKAT DESA MANDING, KELURAHAN SABDODADI, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Cahya Wulandari; Indung Wijayanto (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2016)
The society sometimes uses consensus in solving criminal case. The people of Manding villagge, Bandul district often solve the case of fornication or persecution through deliberation to reach consensus. The settlement contains the values of conservation in the form of fair vales and tolerant so it should be conserved. Based on those condition the statement of the problem is How the accomodation of conservation values in solving the crime in Manding village, Bantul district is? This research is a sociological juridical research. The data used are primary and secondary data. Primary data are obtained through interview, while the secondary data are obtained through literature study. The data obtained then are analyzed using interactive model of analysis. The result of the reseach shows that the accomodated conservation values in solving criminal case inManding village are religious, smart, tough, honest, caring, tolerant, democratic and polite values. Those eight values are reflected in the process of solving the case which prioritize and pay attention to the rights and obligations of the parties.